Research Status and Molecular Mechanism of the Traditional Chinese Medicine and Antitumor Therapy Combined Strategy Based on Tumor Microenvironment - Zhang, Yang; Lou, Yanni; Wang, Jingbin; Yu, Cunguo; Shen, Wenjuan (Frontiers in Immunology, 2021)
Treatment of malignant tumors encompasses multidisciplinary comprehensive diagnosis and treatment and reasonable combination and arrangement of multidisciplinary treatment, which is not a simple superimposition of multiple treatment methods, but a comprehensive consideration of the characteristics and specific conditions of the patients and the tumor. The mechanism of tumor elimination by restoring the body's immune ability is consistent with the concept of "nourishing positive accumulation and eliminating cancer by itself" in traditional Chinese medicine (TCM). The formation and dynamic changes in the tumor microenvironment (TME) involve many different types of cells and multiple signaling pathways. Those changes are similar to the multitarget and bidirectional regulation of immunity by TCM. Discussing the relationship and mutual influence of TCM and antitumor therapy on the TME is a current research hotspot. TCM has been applied in the treatment of more than 70% of cancer patients in China. Data have shown that TCM can significantly enhance the sensitivity to chemotherapeutic drugs, enhance tumor-suppressing effects, and significantly improve cancer-related fatigue, bone marrow suppression, and other adverse reactions. TCM treatments include the application of Chinese medicine monomers, extracts, classic traditional compound prescriptions, listed compound drugs, self-made compound prescriptions, as well as acupuncture and moxibustion. Studies have shown that the TCM functional mechanism related to the positive regulation of cytotoxic T cells, natural killer cells, dendritic cells, and interleukin-12, while negatively regulating of regulatory T cells, tumor-associated macrophages, myeloid-derived suppressive cells, PD-1/PD-L1, and other immune regulatory factors. However, the application of TCM in cancer therapy needs further study and confirmation. This article summarizes the existing research on the molecular mechanism of TCM regulation of the TME and provides a theoretical basis for further screening of the predominant population. Moreover, it predicts the effects of the combination of TCM and antitumor therapy and proposes further developments in clinical practice to optimize the combined strategy.